2014
DOI: 10.1242/bio.20147682
|View full text |Cite
|
Sign up to set email alerts
|

Various applications of TALEN- and CRISPR/Cas9-mediated homologous recombination to modify the Drosophila genome

Abstract: Modifying the genomes of many organisms is becoming as easy as manipulating DNA in test tubes, which is made possible by two recently developed techniques based on either the customizable DNA binding protein, TALEN, or the CRISPR/Cas9 system. Here, we describe a series of efficient applications derived from these two technologies, in combination with various homologous donor DNA plasmids, to manipulate the Drosophila genome: (1) to precisely generate genomic deletions; (2) to make genomic replacement of a DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 36 publications
4
71
0
Order By: Relevance
“…In Drosophila it has been possible for several years to create specific genome modifications by HDR, although targeting typically occurs with very low efficiency (28). Recent studies have suggested that zinc finger, transcriptional activator-like effector (TALE), and Cas9 nucleases can increase the efficiency of HDR in flies, implying that the generation of site-specific DSBs is rate limiting (11,12,27,29,30). Therefore we tested whether the highly effective creation of DSBs by our transgenic CRISPR/Cas system could be exploited to facilitate efficient HDR.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila it has been possible for several years to create specific genome modifications by HDR, although targeting typically occurs with very low efficiency (28). Recent studies have suggested that zinc finger, transcriptional activator-like effector (TALE), and Cas9 nucleases can increase the efficiency of HDR in flies, implying that the generation of site-specific DSBs is rate limiting (11,12,27,29,30). Therefore we tested whether the highly effective creation of DSBs by our transgenic CRISPR/Cas system could be exploited to facilitate efficient HDR.…”
Section: Resultsmentioning
confidence: 99%
“…A homology-independent targeted integration (HITI) strategy without clean junctional DNA sequences has also been reported in Xenopus (Shi et al, , 2017. In all these reports the efficiency of knock-in events for small DNA sequences is low (Miyaoka et al, 2014;Yu et al, 2014), typically ∼1-2%, and although drug selection or cell sorting can be used to recover these rare integration events in cell lines, this is generally not possible in vertebrate models. As a result, CRISPR/HDR-mediated targeted insertion in animal models requires lengthy, tedious screening of F0 founders.…”
Section: Introductionmentioning
confidence: 99%
“…The recent introduction of CRISPR/Cas has made GT via direct injection of donor DNAs plus supporting reagents (e.g., guide RNA) into early embryos possible in Drosophila (BaenaLopez et al 2013; Gratz et al 2013;Bassett and Liu 2014;Port et al 2014;Xue et al 2014;Yu et al 2014). In addition to rapid turnover, direct embryo injection allows easy adoption of diverse GT strategies.…”
Section: Discussionmentioning
confidence: 99%
“…With CRISPR/Cas9, direct embryo injection for ends-out GT in Drosophila has been demonstrated (Baena-Lopez et al 2013;Gratz et al 2013;Port et al 2014;Xue et al 2014;Yu et al 2014) (Figure 1B). This saves the 2 months needed for the initial transgenesis of the donor DNA and may eliminate the need for complex selections.…”
mentioning
confidence: 99%